Psychological impacts caused by domestic violence: Integrative literature review (Research, Society and Development, 2022)
Domestic violence, also known as intrafamily violence, is a current issue in the world, which must always be debated, deconstructing the discourses that support this type of practice. The objective of this research is to portray the impacts caused on the quality of life of women who suffer domestic violence, as well as the victims' recovery strategies. The study is an integrative literature review, through a search in the SCIELO, LILACS and PUBMED databases, in the period of publication between the years 2015 and 2022. Using the Boolean operator "OR" or "or" and through of articulations of the keywords: “Impacts of domestic violence”, “Domestic violence OR psychological impacts OR women”, “Women victims of domestic violence”. Articles selected from the chosen databases were subjected to careful analysis, according to the inclusion and exclusion criteria, based on the proposed theme. The impacts caused by violence can often cause irreversible damage to victims. Although there are numerous organizations focused on helping these women victims of aggression, we still see a need for means of prevention and protection that can, in a more practical and effective way, reduce the obstacles they face every day to escape situations. risks arising from partner violence.